Auditor Performance from the Perspective of Independence and Professional Ethics: Factors Affecting the Decline in Audit Quality - Serilia Tangalayuk; Aunneke Julisda Paembonan; Nurhikmah Dewi Anugrah; Amiruddin Amiruddin (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyse auditor performance from the perspective of independence and professional ethics as determining factors in preventing reduced audit quality practices (RAQP). This study focuses on understanding how these two dimensions interact to influence professional behaviour and audit credibility. This study uses a Systematic Literature Review (SLR) approach with the Watase Uake method to identify and synthesise previous studies relevant to auditor performance, independence, ethics, and audit quality decline. Data were collected from Scopus-indexed journals (Q1–Q4) and other international sources between 2020 and 2025, resulting in 33 relevant articles selected through a structured screening process and thematic analysis. Findings indicate that auditor independence significantly influences performance quality by maintaining professional scepticism and objectivity, while professional ethics reinforce moral responsibility and integrity in decision-making. The main threats to audit quality stem from client pressure, time constraints, and role conflicts that trigger dysfunctional behaviours such as reducing audit quality practices (RAQP). Conversely, a strong ethical culture and effective organisational governance can minimise these risks. This study provides insights for audit firms, regulators, and educational institutions to strengthen ethical culture, develop resilience training, and implement strict independence policies to improve audit quality and public trust in the accounting profession. This research offers a comprehensive synthesis linking independence and professional ethics as two determinants of auditor performance and audit quality—areas that have often been explored separately in previous studies.